OPPORTUNITIES OF IMPLEMENTING OUTDOOR EDUCATION IN YOUTH WORK: ON THE EXAMPLE OF TALLINN YOUTH CENTRES - Veigel, Maarika; Reedik, Triinu (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Nature as a natural living environment is important in the development of young people, but their lifestyle doesn’t support it. Youth workers have a major role in guiding young people to interesting activities in nature and outdoor, sharing relevant information as well as being an example. The research problem: what kind of opportunities were given to the youth, spending time in Tallinn youth centres, to participate in outdoor activities in the youth workers opinions and how to improve them? The aim of the research was to map the opportunities and needs to implement outdoor education in youth work in order to arouse interest in outdoor activities among the youth.For qualitative data collection semi-structured interviews were carried out (in February, 2015) in nine Tallinn youth centres out of ten. Therefore, the results can be generalized to all Tallinn youth centres. It was found that different opportunities for implementing outdoor education were used in Tallinn youth centres, but a large part of the potential is still unused. The workers in Tallinn youth centres feel the need to receive training about the methods, games and use of technical and interactive devices in carrying out outdoor activities for the youth.